Average Contact Temperature and Morphological Details of the Worn Surface of Copper Based Materials under High Current Density Sliding against Steel; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Fadin V. V. (2016, 2016)
Title screen